The Effects of Education, Minimum Wages, and Life Expectancy On Female Labor Force Participation Rates Across Regencies/Municipalities In Bali Province, 2018-2025 - Anggi Dwi Lestari; Mohammad Wasil (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the effects of education, minimum wages, and life expectancy on the female labor force participation rate (FLFPR) across the regencies and municipality of Bali Province during 2018-2025. The study uses secondary panel data covering nine regencies/municipalities and 72 observations. Panel data regression was employed using the Fixed Effects Model (FEM), selected through the Chow and Hausman tests. The findings indicate that education, minimum wages, and life expectancy jointly have a significant effect on the female LFPR, with a coefficient of determination of 71.46%. Partially, education has a positive and significant effect on the female LFPR, whereby each one-year increase in mean years of schooling increases the female LFPR by 522.93%. Minimum wages have a negative and significant effect, whereby each IDR 1,000 increase in the regency/municipal minimum wage reduces the female LFPR by 0.0005588%. Life expectancy has a positive but statistically insignificant effect on the female LFPR. These findings are consistent with Human Capital Theory, which posits that investment in education enhances productivity and labor market participation. The study recommends that local governments expand women's access to education and formulate minimum-wage policies that support female-intensive sectors to promote women's labor force participation in Bali Province.